Liaisons between culture and innovation: comparative analysis of South Korean and Lithuanian IT companies - Mindaugas Laužikas; Aistė Miliūtė (Insights into Regional Development)
The present publication is centred on the key liaisons of Innovation (Kane et al. 2019, Marwede and Herstatt 2019, Kremer et al. 2019, Narayan, 2019, Lauzikas and Miliute 2017, 2019a, 2019b, and etc.) and Culture (Lauzikas and Mokseckiene 2013, Boon et al. 2019, ASUG, 2019, Clercq and Pereira 2019, and etc.) as two separate components of innovation climate aas well as the main effects of combination of these dimensions on business sustainability (Collett et al. 2019, Halim et al. 2019, Sull et al. 2019, Jin et al. 2019, and etc.). The research problem is how to acknowledge and excel in the areas, related to ‘Innovation-Culture Symbiosis’, without limiting the progress of innovation or human resource management as separate departments and not stopping a firm from strengthening its competitive advantages, driven by the combination of these dimensions. This is relevant and innovative, because nowadays a great number of efficiency and innovation-driven economies or high-tech industries face the necessity to identify, acknowledge and mitigate weaknesses in human resource or R&D performance as well as link these dimensions towards innovation culture via modern technologies, innovative managerial processes, strategic collaboration and creative leadership. The purpose of the present paper: comparing the key dimensions of ‘Innovation-Culture Symbiosis’ in high-tech firms of South Korea and Lithuania (both are education-driven countries) it is expected to illustrate the dynamics of a holistic system of innovation and culture, where these two dimensions are interdependent and form a unique equilibrium (which corresponds to a specific economic and business development stage, position in the value-chain as well as cultural and social norms of a country). Taking into account that sustainable business calls for continuous improvement of products and processes via HRM techniques, R&D, innovation and technology, the present research results are pertinent and value-adding to high-tech companies of both economies: they could help reach healthier equilibrium between innovation and culture within a specific socio-economic context, and contribute to the establishment of monitoring models which track the dynamics of innovation culture and lead to the bigger economic and social value-added. Taking into consideration the trans-disciplinary holistic nature of innovation culture, which requires a rich knowledge and experience within the present topic, the semi structured interviews with experts of Lithuanian and South Korean IT firms were conducted, the research results of the two economies were compared, and recommendations were provided for both high-tech experts and governmental policy or program developers.